MANAGEMENT OF ADVERSE REACTIONS TO ALEMTUZUMAB INFUSION. Issue 11 (14th October 2015) - Sharrack, Basil; Mayer, Lori; Coles, Alasdair; Hartung, Hans-Peter; Havrdova, Eva; Selmaj, Krzysztof; Margolin, David; Compston, Alastair
Abstract : In the 2-year, phase 3 CARE-MS studies of alemtuzumab in patients with relapsing-remitting multiple sclerosis, infusion-associated reactions (IARs) were the most common adverse events. Here we report on IARs during 4-year follow-up. Patients who were treatment-naive (CARE-MS I; NCT00530348 ) or with inadequate efficacy response to prior therapy (CARE-MS II; NCT00548405 ) received 2 annual courses of alemtuzumab 12 mg, and as-needed retreatment in an extension study (NCT00930553 ). Patients received methylprednisolone on the first 3 days of each course. IARs were any adverse event occurring between start of infusion and within 24 hours after end of infusion. 742/811 alemtuzumab-treated patients entered extension. Over 4 years, 70.4% received only 2 initial treatment courses; 22.6% and 6.1% received 3 and 4 courses, respectively. IARs were most frequent in Course 1 (84.7%) versus Courses 2 (68.5%), 3 (65.7%), and 4 (71.1%); frequency decreased on infusion Days 2 and 3 versus Day 1. IARs were predominantly mild to moderate; none led to study withdrawal or death. Serious IAR incidence was 3.1%. Most common IARs were skin disorders (predominantly rash), headache, pyrexia, and nausea. One confirmed anaphylaxis and one non-anaphylactoid hypotension event resolved with treatment. Effective IAR management included premedication, infusion monitoring, symptomatic treatment, and infusion interruption/adjustment.